Post-traumatic liver pseudocyst, portal thrombosis, hemobilia - Delgado, Bolívar; Praderi, Raúl; Cassinelli, Daniel (Cirugía del Uruguay, 2020)
The paper presents a case of . tráumatic hemobilia in a patient in whom the extrahepatic development of a post-traumatic pseudo cyst resulted in a compression of the main hepatic hile duct and the portal vein causing its thrombosis. Therapy involved drainage of the cavity and l igation of the right branch of the hepatic artery. The treatment to be followed in cases such as this, is discussed.